2021
DOI: 10.1038/s41598-021-97435-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells as carriers of IL-12 reduce primary and metastatic tumors of murine melanoma

Abstract: Due to immunosuppressive properties and confirmed tropism towards cancer cells mesenchymal stromal cells (MSC) have been used in many trials. In our study we used these cells as carriers of IL-12 in the treatment of mice with primary and metastatic B16-F10 melanomas. IL-12 has confirmed anti-cancer activity, induces a strong immune response against cancer cells and acts as an anti-angiogenic agent. A major limitation of the use of IL-12 in therapy is its systemic toxicity. The aim of the work was to develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Some evidence supports the involvement of in ammatory signals in cancer as environmental cues in MSCs migration and biodistribution paradigm [15]. Previous research has shown that reducing tumor load and extending the lifespan of animal studies of melanoma, lung, breast cancer, and glioma using MSC expressing IL-12, interferon-β (IFN-β), and prodrugs [16][17][18].…”
Section: Introductionmentioning
confidence: 94%
“…Some evidence supports the involvement of in ammatory signals in cancer as environmental cues in MSCs migration and biodistribution paradigm [15]. Previous research has shown that reducing tumor load and extending the lifespan of animal studies of melanoma, lung, breast cancer, and glioma using MSC expressing IL-12, interferon-β (IFN-β), and prodrugs [16][17][18].…”
Section: Introductionmentioning
confidence: 94%
“…25,26 MSCs can be easily genetically engineered and used as biofactory for the local production of chemo and biological anticancer therapeutics at the tumor sites to overcome the challenges related to the systemic administration of anticancer therapeutics with a short half-life or high toxicity. [26][27][28] MSCs have been used for the delivery of chemotherapeutics and biological anticancer therapeutics such as genes encoding prodrug-activating enzymes, 29,30 cytokines, 31,32 oncolytic viruses, 9,33 among others. Therefore, MSCs emerged as a versatile tumor delivery vehicle in precision cancer treatment technologies for different cancers.…”
Section: Prominent Intrinsic Properties Of Msc As a Versatile Tumor D...mentioning
confidence: 99%
“…Inflammation is a common feature of tumor tissues. 57 The tumor-tropism capability of MSCs toward several cancer cell lines such as melanoma, 31 colon cancer, 58 pancreatic cancer, 59 ovarian cancer, 60 breast cancer, 61 Kaposi's sarcoma, 20 lung cancer, 62 and malignant glioma 63 has been demonstrated. The tumor-tropism of MSCs is not limited to primary or solid tumors.…”
Section: Tumor-tropism Featurementioning
confidence: 99%
See 1 more Smart Citation
“…Intratumoral gene electroporation uses electric charges to help plasmid DNA enter target cells reproductively and effectively, especially in metastatic melanomas [ 33 ]. Other than gene electroporation, lipid nanoparticles [ 51 ], dual-targeting nanoparticles [ 80 ], hypoxia-responsive nanogel [ 81 ], cationic polyphosphazene vesicles [ 82 ], collagen [ 37 ] and heparin-based complex coacervate [ 23 ] were also developed to allow more efficient delivery as IL-12 or IL-12 encoding plasmid carrier, despite the artificial chemicals, mesenchymal stromal cells [ 83 ] and DCs [ 84 ] overexpressing IL-12 exert therapeutic properties of IL-12 cytokine without toxicity. Great efforts should be made in the future to further improve the anti-tumor efficacy and diminish the side effects of IL-12 therapy.…”
Section: Strategies To Reduce the Immune-related Side Effects Of Il-1...mentioning
confidence: 99%